Investigation into the Impact of Humidity on Early Age Cement Concrete Pavement Behavior in Hot and Humid Regions - Min Chai; Lijuan Wang; Changbin Hu; Tao Chen (Applied Sciences, 2023)
Cement concrete pavement is prone to early deterioration during the construction phase, and the early performance during the construction phase is significantly affected by the external temperature and humidity field. This article selects meteorological parameters in the Fuzhou area as a typical representative of a humid and hot climate and develops a three-dimensional humidity simulation program based on Fick’s law and the finite difference method to study the evolution behavior of the humidity field in early age of cement concrete pavement. It discusses the humidity distribution characteristics of road panels and analyzes the influence and sensitivity of cement type, construction conditions, and road panel structural parameters on road panel humidity. Research has shown that the evolution law of the humidity field of road panels shows a 24-h periodic change with the external environment. The environmental field has a significant impact on the surface humidity of road panels. The horizontal humidity of the panel is concentrated from the boundary to the middle of the panel, and the tangential humidity is concentrated from the top to the bottom of the panel. The humidity field of road panels is the most sensitive to environmental humidity and maintenance methods, but less sensitive to material and structural parameters. Therefore, during construction, it is possible to avoid the hot season and choose a time period when the environmental humidity increases to pour concrete. Appropriate maintenance methods are adopted to reduce the humidity stress of the panels, reduce early age deterioration, and improve their service life.